Determinants Affecting Customers’ Satisfaction Based on Logistics Services: A Case Study of Logistics Companies in Vietnam - Tam, Phan Thanh (International Journal of Supply Chain Management, 2020)
This study aims to determine the factors affecting customer satisfaction with logistics enterprises’ logistics services in Vietnam. Data collected through survey questionnaires sent to customers who are currently using the services of businesses. Research has shown eight factors affecting customer satisfaction, including tangible factors, reliability, guarantee, empathy, responsiveness, perceived price, customer relationship service, and relationship quality-these eight factors measured through 35 observed variables. The authors had conducted a study the Data from 750 customers related to 50 logistics companies in Vietnam. The authors used the SEM model for Data analysis. The authors had the factors affecting customer satisfaction that will help businesses better understand customer needs and then have a strategy to improve customer satisfaction